Environmental impact assessment: Kirindi Oya Irrigation and Settlement Project (KOISP). Draft final report - Amarasekara, N. (International Irrigation Management Institute, 1991)
The Kirindi Oya river basin development/degradation however has been planned in two different ways, namely, downstream, where the Kirindi Oya Irrigation and Settlement Project (KOISP) is located and the upper catchment where contemporary environmental degradation occurred. This review is based on that belief, inspite of limitations in data macro hydrological studies covering larger river basins would, at least, for reconnaissance purposes, prove equally useful as the more common micro catchment studies. Due to negligence and lack of knowledge of the importance of watershed management in the Kirindi Oya basin, there is considerable damage in downstream in the Kirindi Oya basin where the KOISP is operated. It is necessary, therefore, to consider contemporary environmental degradation in both downstream and watershed separately.